2018
DOI: 10.1161/hypertensionaha.118.11303
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Suppression of Aldosterone Production Leads to Salt-Sensitive Hypertension in Female but Not Male Balb/C Mice

Abstract: Clinical studies indicate that salt-sensitive hypertension is more prevalent in women than men. However, animal models of salt-sensitivity have primarily focused on the mechanisms of salt-sensitivity in male animals, therefore, elucidation of these mechanisms in female animal models are needed. We have previously shown that female Balb/C mice have higher aldosterone synthase expression and aldosterone production than males. We hypothesized that female Balb/C mice develop salt-sensitive increases in blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 41 publications
(58 reference statements)
4
40
0
Order By: Relevance
“…Moreover, Bier et al (2018) demonstrated a significant association between gut microbiota composition and blood pressure regulation; even the metabolic short-chain fatty acids (SCFAs) may highlight another aspect of the complex interaction between diet, gut, and blood pressure. Additionally, it has been suggested that gut microbiota composition and microbial metabolites are the potential mediators between a single gene associated with blood pressure regulation and hypertension (Faulkner et al, 2018;Waghulde et al, 2018;Yang et al, 2018). In the present study, we found that ATF4 could regulate the gut microbiota composition and the expression of VK2 in hypersensitive mice induced by high-salt diet, suggesting that the mechanisms of ATF4 involved in blood pressure regulation and the vascular endothelial function may be related to gut microbiota and VK2.…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, Bier et al (2018) demonstrated a significant association between gut microbiota composition and blood pressure regulation; even the metabolic short-chain fatty acids (SCFAs) may highlight another aspect of the complex interaction between diet, gut, and blood pressure. Additionally, it has been suggested that gut microbiota composition and microbial metabolites are the potential mediators between a single gene associated with blood pressure regulation and hypertension (Faulkner et al, 2018;Waghulde et al, 2018;Yang et al, 2018). In the present study, we found that ATF4 could regulate the gut microbiota composition and the expression of VK2 in hypersensitive mice induced by high-salt diet, suggesting that the mechanisms of ATF4 involved in blood pressure regulation and the vascular endothelial function may be related to gut microbiota and VK2.…”
Section: Discussionsupporting
confidence: 62%
“…Excised thoracic aortas were cleaned of adipose tissue, cut in 2 mm rings, and mounted on DMT® wire myograph (Ann Arbor, MI). Concentration-response curves to phenylephrine, serotonin, sodium nitroprusside, and acetylcholine in the presence or absence of the nitric oxide synthase (NOS) inhibitor Nω-Nitro-L-arginine methyl ester hydrochloride (LNAME, 100 μM, 20 min preincubation) as well as maximum responses to KCl were performed and recorded with the LabChart® analysis software (AD Instruments®, Colorado Springs, CO) as previously described (1 nM-30 μm concentrations) [ 7 , 13 , 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Proteins were transferred to nitrocellulose membranes and stained for CYP11B2 (aldosterone synthase, antibodies generously supplied by Drs. Elise and Celso Gomez-Sanchez, University of Mississippi Medical Center) and β-actin as previously described [ 7 , 13 ]. In addition, RNA was isolated (Qiagen® minikit, Germantown, MD) from homogenates in Trizol (ThermoFisher®, Waltham, MA) followed by reverse transcription to obtain cDNA (ThermoFisher®, Waltham, MA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations